Perancangan Sistem Informasi Kepegawaian Pada PT SIMASJESS MULTIDAYA SOLUSI - Dwiki Surya Gandi; Lisa Amelia Fransen (Cattleya Darmaya Fortuna, 2025)
PT Simasjess Multidaya Solusi is located at Jl. Yayasan I No.1870, Sei Buah, Kec. Ilir Tim. II, Palembang City, South Sumatra 30116. PT Simasjess Multidaya Solusi is a company engaged in the creative agency and digital world that has been established since 2013. The problems faced by PT Simasjess Multidaya Solusi include the recruitment process, absence, leave, permits, rewards, punishments. Therefore, the creation of this personnel system application aims to help the business process of PT Simasjess Multidaya Solusi by using the Ration Unified Process (RUP) method which can develop a simple Personnel System and has an easy-to-understand concept for the business process of PT Simasjess Multidaya Solusi. The findings of this study explain that by implementing a personnel system with the RUP method, PT Simasjess Multidaya Solusi can make better decisions regarding rewards, punishments, promotions, demotions, and layoffs. Not only does it make better decisions, the personnel system also makes it easier for employees in terms of attendance, leave, and permits, and also makes it easier for prospective employees to apply.